Smart Highways Based Vehicle Speed Sensor With Piezoelectric Energy Harvesting: A Progress Report - Rall, Keven Charles; Bailen, Kara Leah; Bender, Elizabeth Nicole; Taha, Luay Yassin; Abdeltawab, Hussein M; Anwar, Sohail (IEEE International Conference on Industrial Technology (Online), 2023)
Smart highway and smart road are terms for several different ways of technologies that are incorporated into roads, for improving the operation of connected and autonomous vehicles (CAVs), In our previous work, we completed the design and testing of the preliminary piezoelectric road energy harvester prototype. The prototype outputs electrical pulses when stressed by a vehicle. The aim of this paper is to present our progress work in designing a piezoelectric harvester and speed sensor by embedding, in the asphalt, two piezoelectric modules at a known distance. Each one generates pulses when stressed by the vehicle wheels. These pulses are sent to the Arduino microcontroller. The time delay between the pulses is then estimated using time delay estimation algorithm, then the vehicle speed is computed from the distance to time ratio. The sensing pulses are also converted to DC and used to charge the microcontroller battery. The system is tested for different vehicle speeds. Results have shown considerable accuracy in sensing the vehicle speed when varied from 10 km/h to 240 km/h, and when the input signal-to-noise ratio is varied from 10 dB to 100 dB.